A REVIEW OF POTENTIAL LUNG ORGANOIDS EXPLORATION AND CLINICAL APPLICATIONS - KONDA, BINDU; DEPURU, BHARATHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In recent years, the mortality rate remains unacceptably high despite many advancements made in the field of lung-related diseases. This can be attributed to the lack of current preclinical models and the inability to translate fundamental epithelial studies into clinical therapy. Three-dimensional cultures have properties present in stem cells, such as the ability to self-organize in matrices and able to generate structures that can be reprogrammed to represent an organ or a pathology. By adding source tissue ranging from cells to tissue fragments to a support matrix and specialized media, the generation of 3D organoid cultures are achieved resembling the physiological environment of the tissue’s origin. Depending on the source tissue, growth factors, and inhibitors provided, organoids can be programmed to recapitulate the biology of a system and the progression of a pathology. In this review, the main objective is to discuss recent technical advances that efficiently use organoids as a tool for disease modeling, regenerative medicine, toxicology studies, therapeutics and various techniques used for large scale organoid generation. Using animal models for drug screening and toxicology studies has certain drawbacks, but organoids can help to overcome these obstacles. The advantages of stem cell-derived organoid models in comparison to current culture systems are highlighted, recent developments in tissue-based organoids are becoming specialized models for studies related to human translation medicine.